2006
DOI: 10.1179/026708306x81522
|View full text |Cite
|
Sign up to set email alerts
|

Development of tubular transition joints of aluminium/stainless steel by deformation diffusion bonding

Abstract: Joining of aluminium and aluminium alloys to stainless steel is frequently required in many low temperature and nuclear applications. The present study describes a relatively new method of bonding these materials by suitably combining the deformation bonding and solid state bonding techniques for joining tubular assemblies. The stainless steel and aluminium specimens have been machined to form cylindrical tube specimens and special grooves have been machined on the inner diameter (ID) side of the stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This shows that the capability of FOW is comparable to FRW and DFW, 8,9 and that FOW is efficient in welding the stainless steel and aluminium alloy within several seconds. Regarding to the effect of T and d on the s, the s had no great improvement when the T was increased from 350 to 400uC, because the heat energy was insufficient to fully activate the diffusion between particles inside the two dissimilar metals, and the intermetallic bond was incomplete.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…This shows that the capability of FOW is comparable to FRW and DFW, 8,9 and that FOW is efficient in welding the stainless steel and aluminium alloy within several seconds. Regarding to the effect of T and d on the s, the s had no great improvement when the T was increased from 350 to 400uC, because the heat energy was insufficient to fully activate the diffusion between particles inside the two dissimilar metals, and the intermetallic bond was incomplete.…”
Section: Resultsmentioning
confidence: 78%
“…In the FOW experiments, the tensile strengths s of the three joints produced at T5450uC could exceed 100 MPa, which was much stronger than the results obtained by Bhanumurthy et al, 9 and hence the fractures occurred in AA6063 regions. This shows that the capability of FOW is comparable to FRW and DFW, 8,9 and that FOW is efficient in welding the stainless steel and aluminium alloy within several seconds.…”
Section: Resultsmentioning
confidence: 81%
“…Forge‐welding and uniaxial tensile tests were carried out. The results showed that four bimetallic joints among 36 specimens were stronger than those obtained by Bhanumurthy et al [10]. Besides, the processing time of those forge‐welding processes was only a few seconds.…”
Section: Effects Of Process Parametersmentioning
confidence: 71%
“…The tensile strength of the quality joint was higher than that of the aluminium alloy. Bhanumurthy et al [10] investigated the diffusion bonded stainless steel and aluminium alloy specimens carried out at 315 °C for 4 h. An excellent bonding with the tensile strength of 91 MPa and total absence of the intermetallic compounds in the reaction zone were indicated.…”
Section: Introductionmentioning
confidence: 99%
“…There was no doubt about their weldability since previous researchers[29][30][31][32] had reported that such combinations of dissimilar metals could be joined by solid-state welding. If two metals are welded successfully, a narrow diffusionFig.…”
mentioning
confidence: 99%